This comes from an extra-credit question in my math class.
Prove: \( \vec a \times (\vec b \times \vec c) = (\vec a * \vec c)\vec b - (\vec a * \vec b)\vec c \)
I can prove it alternatively by manipulating the components algebraically with determinant calculations, but such an approach doesn't make any intuitive sense, and after all, it's boring.
Proof:
Let \( \vec a = |a|e_a , \vec b = |b|e_b , \vec c = |c|e_c, \) where e is a unit vector of length 1.
\(\vec a \times (\vec b \times \vec c) = |a||b||c|(e_a \times ( e_b \times e_c))\)
\((\vec a * \vec c)\vec b - (\vec a * \vec b)\vec c=|a||b||c|((e_a * e_c)e_b - (e_a * e_b)e_c)\)
Therefore, we need to show \(e_a \times ( e_b \times e_c)=(e_a * e_c)e_b - (e_a * e_b)e_c\).
Define \(e_{\perp b}=\frac{c-(c*e_b)e_b}{|c-(c*e_b)e_b|}\), \(e_{b\times c} \) as \( \frac{b \times c}{|b \times c|}\).
Then \(e_b\), \(e_{\perp b}\), and \(e_{b\times c}\) forms an orthonormal basis in \(R^3\).
![]() |
The basis vectors are shown in red |
$ =(x,y,z) \times (0,0,\sin{\theta_{cb}})$
$ =(y\sin{\theta_{cb}},-x\sin{\theta_{cb}},0)$
$ =(y\sin{\theta_{cb}},0,0)-(0,x\sin{\theta_{cb}},0)$
$ =(x\cos{\theta_{cb}}+y\sin{\theta_{cb}},0,0)-(x\cos{\theta_{cb}},x\sin{\theta_{cb}},0)$
$ =(a'*c',0,0)-(x\cos{\theta_{cb}},x\sin{\theta_{cb}},0)$
$ =(a'*c')(1,0,0)-(x\cos{\theta_{cb}},x\sin{\theta_{cb}},0)$
$ =(a'*c')b-(x\cos{\theta_{cb}},x\sin{\theta_{cb}},0)$
$ =(a'*c')b-x(\cos{\theta_{cb}},\sin{\theta_{cb}},0)$
$ =(a'*c')b-xc'$
$ =(a'*c')b-(x,y,z)*(1,0,0)c'$
$ =(a'*c')b-(a'*b')c'$
With this reference, we have the following: For an orthogonal matrix $A$, \[A\vec x \times A\vec y = \det (A)*A(x \times y),\ \det (A)=\pm 1 \]\[A\vec x * A\vec y=x*y\]
Since $S$ is orthogonal, it applies to $S$.
Because $ a' \times (b' \times c')=(a'*c')b-(a'*b')c'$
Therefore $ S(a' \times (b' \times c'))=S((a'*c')b-(a'*b')c')$
Therefore $ e_a \times ( e_b \times e_c)=(e_a * e_c)e_b - (e_a * e_b)e_c$
$ \Box$
No comments:
Post a Comment